Resistance of Synthetic and Biologic Surgical Meshes to Methicillin-Resistant Staphylococcus aureus Biofilm: An In Vitro Investigation - Ethan Kallick; Laura Nistico; Mark Longwell; Barbara Byers; Frank Cartieri; Rachael Kreft; Howard Edington (International Journal of Biomaterials)
Surgical meshes have become the standard procedure for a variety of surgical applications with 20 million meshes being implanted each year. The popularity of mesh usage among surgeons is backed by the multiple studies that support its functionality as a tool for improving surgical outcomes. However, their use has also been associated with infectious surgical complications and many surgeons have turned to biologic meshes. While there have been several studies investigating synthetic meshes, there is limited data comparing synthetic and biologic meshes in vitro in an infection model. This study evaluates the in vitro susceptibility of both synthetic and biologic meshes to single-species methicillin-resistant Staphylococcus aureus (MRSA) biofilms. This research compares biofilm biomass, average thickness, and coverage between the three meshes through florescent in situ hybridization (FISH), confocal scanning microscopy (CSLM), and image analysis. We also report the varying levels of planktonic and attached bacteria through sonication and cfu counts. While the data illustrates increased biofilm formation on biologic mesh in vitro, the study must further be investigated in vivo to confirm the study observations.